Treatment adherence in patients older than 65 years who suffer early readmissions - Sergio Vicente-Sánchez; Raquel Olmos-Jiménez; Cristina Ramírez-Roig; María José García-Sánchez; Manuel Valderrey-Pulido; Amelia de la Rubia-Nieto (Farmacia Hospitalaria)
Objective: Analyze the frequency of therapeutic noncompliance in patients who suffer early readmissions, and identify the factors associated with it. Method: Observational, descriptive study of three months duration (March - May 2014). All patients older than 65 years who readmitted in the 3-30 days following the last hospital discharge were included. We excluded programmed re-admissions and readmissions in the Intensive Care Unit. The variables collected were: age, sex, medical service, major diagnostic category, polypharmacy, number of days since the last hospital discharge, presence of hypertension and/or diabetes. The therapeutic compliance and the difficulty in the administration of medication were evaluated by means of the Morisky-Green test and the Haynes-Sackett test respectively. A descriptive analysis of the variables was carried out and they were related to the therapeutic adherence. The variables with statistical significance were included in a multivariate logistic regression model. Results: Fifty seven percent of the patients presented lack of adherence to pharmacological treatment. Twenty three percent had difficulty administering the medication. Eighty six percent had comorbidities (hypertension and/or diabetes) and 79% had a caregiver. Eighty six percent of patients were polymedicated (≥ 5 drugs). There is a relationship between lack of adherence and difficulty in the administration of medications (p=0.021), polypharmacy (p=0.002), and the presence of diabetes mellitus (p=0.018). Conclusions: Polymedication, the presence of diabetes mellitus and the existence of difficulty in the administration of medication are evidenced as prognostic factors of the lack of adherence to treatment in patients older than 65 years.